2021
DOI: 10.1002/hpm.3241
|View full text |Cite
|
Sign up to set email alerts
|

Resource generation challenges for burn care in Iran

Abstract: Background: Given the importance of investment in human and physical resources and knowledge in burn injuries for improving health service performance, this study endeavoured to identify resource production challenges in the burn care of Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The studies were conducted in 11 nations: Iran (Bijani & Mohammadi, 2021 ; Shaarbafchizadeh et al, 2021 ; Shivanpour et al, 2020 ), Ghana (Bayuo, 2018 ; Bonsu et al, 2019 ), the United States (Rimmer et al, 2015 ), Australia (Kornhaber & Wilson, 2011a , 2011b ), Ireland (Hilliard & O'Neill, 2010 ), Norway (Lernevall et al, 2021 ), the Netherlands (Boersma‐van Dam et al, 2021 ; Suurmond et al, 2020 , 2012 ), Sweden (Bäckström et al, 2018 ; Willebrand & Sveen, 2016 ), the United Kingdom (Heath et al, 2018 ), Canada (Bond et al, 2017 ) and Brazil (de Oliveira et al, 2015 ). The above comprised 11 qualitative studies (Bäckström et al, 2018 ; Bayuo, 2018 ; Bijani & Mohammadi, 2021 ; de Oliveira et al, 2015 ; Heath et al, 2018 ; Hilliard & O'Neill, 2010 ; Kornhaber & Wilson, 2011a , 2011b ; Lernevall et al, 2021 ; Shaarbafchizadeh et al, 2021 ; Shivanpour et al, 2020 ; Suurmond et al, 2012 ), one mixed‐method (Suurmond et al, 2020 ), and 5 quantitative studies (Boersma‐van Dam et al, 2021 ; Bond et al, 2017 ; Bonsu et al, 2019 ; Rimmer et al, 2015 ; Willebrand & Sveen, 2016 ). MMAT was used to evaluate the quality of the included studies, with ratings of 100% (two studies), 80% (six studies), 60% (six studies) and 40% (three studies).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies were conducted in 11 nations: Iran (Bijani & Mohammadi, 2021 ; Shaarbafchizadeh et al, 2021 ; Shivanpour et al, 2020 ), Ghana (Bayuo, 2018 ; Bonsu et al, 2019 ), the United States (Rimmer et al, 2015 ), Australia (Kornhaber & Wilson, 2011a , 2011b ), Ireland (Hilliard & O'Neill, 2010 ), Norway (Lernevall et al, 2021 ), the Netherlands (Boersma‐van Dam et al, 2021 ; Suurmond et al, 2020 , 2012 ), Sweden (Bäckström et al, 2018 ; Willebrand & Sveen, 2016 ), the United Kingdom (Heath et al, 2018 ), Canada (Bond et al, 2017 ) and Brazil (de Oliveira et al, 2015 ). The above comprised 11 qualitative studies (Bäckström et al, 2018 ; Bayuo, 2018 ; Bijani & Mohammadi, 2021 ; de Oliveira et al, 2015 ; Heath et al, 2018 ; Hilliard & O'Neill, 2010 ; Kornhaber & Wilson, 2011a , 2011b ; Lernevall et al, 2021 ; Shaarbafchizadeh et al, 2021 ; Shivanpour et al, 2020 ; Suurmond et al, 2012 ), one mixed‐method (Suurmond et al, 2020 ), and 5 quantitative studies (Boersma‐van Dam et al, 2021 ; Bond et al, 2017 ; Bonsu et al, 2019 ; Rimmer et al, 2015 ; Willebrand & Sveen, 2016 ). MMAT was used to evaluate the quality of the included studies, with ratings of 100% (two studies), 80% (six studies), 60% (six studies) and 40% (three studies).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the interviewed nurses indicated that patients' mistrust occasionally worsened their strain, and some nurses even experienced nighttime nightmares that had a significant influence on their lives and careers. It is important for nurses to take measures such as psychological support or counselling to realign work–life balance (Shaarbafchizadeh et al, 2021 ; Shivanpour et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations